Thermal Analysis of the Soft Segment (SS) Glass Transition of Diacetylene-containing Polyurethanes (DA-coPUs) - Widayani Sutrisno (Indonesian Journal of Physics, 2005)
The glass transition of a two-phase polymer, Diacetylene Containing Polyurethanes (DA-coPUs) containing 50%-by-weight hard-segments made from polyol Voranol EP 2001, isocyanate methylene diphenylene diisocyanate (MDI), and chain extender 2,4-hexadiyne-1,6-diol (HDD) has been analysed using Differential Scanning Calorimetry (DSC), Temperature Modulated DSC (MDSC) and Dynamical Mechanic Thermal Analysis (DMTA) measurements. The temperature of the glass transition of the DA-coPUs is mainly influenced by the polyol, showing a Tg of –72°C. The presence of isocyanate and short diol resulted in increasing Tg by about 25 °C. Tg values observed from DMTA measurements were higher than that from DSC and TMDSC measurements by about 10 and 15 °C, respectively. After cross-polymerisation of the DA-coPUs, the temperature of the glass transition was increased by about 8-10°C, showing the effect of polydiacetylene formation in the DA-coPUs.